AKTUALISASI NILAI-NILAI PANCASILA PADA ERA REVOLUSI INDUSTRI 4.0 - Vieto Budi Utomo; Slamet Widodo (Journal of Professional Elementary Education, 2023)
Pancasila is the state ideology and an important reference for all Indonesian people. The noble virtues of Pancasila values ​​in the industrial era 4.0 were eroded by advances in science, technology, and art that were not filtered properly. Indications of the waning of Pancasila values ​​in the industrial era 4.0 can be seen from the increasing number of cases involving the nation's generation, which reflect the weakness of the nation's character, such as increasing crime, corruption, collusion and nepotism, radicalism, sexual crimes, consumptive life, political life that is not productive, etc. Efforts are needed to actualize Pancasila in the life of society, nation and state. By socializing the actualization of Pancasila values ​​in the industrial era 4.0, so that the credibility of Pancasila can be maintained in increasing awareness and responsibility of the nation's generation for a quality, intelligent, and characterized future. This research was conducted by using the method of literature review or literature review.